Originally Posted by

**Parton-Bill** Hi all, Many thanks to those who have offered valued help to my other posts.

I think i'm starting to get the hang of this math lark (Itwasntme)

Ok, down to the question, i have several questions that i have done my best to answer, I wondered if anyone would mind just looking over them for mistakes or wrong use of solutions please?

(i) Solve by Factorization of quadratic formula:

x(2) + 6x + 8 = 0

By Factorization: (x + 4) (x + 2) = 0

X = -4 X = -2 ........ **OK**

By Quadratic Equation:__ -b__ +- __sqrt b(2) - 4ac__

2a 2a

__- 6__ +- __sqrt 6(2) - (4x1x8)__

2x1 2x1

= -3 +- __2__

2

X = -4 X = -2. ........ **OK**

.................................................. ................................................

(ii) 2x(2) + 11x + 14 = 0

Using Quadratic Equation:

__- 11__ +- __sqrt 11(2) - (4 x 2 x 14)__

2x2 2x2

= -2.75 +- __3__

4

x = -3.5 x = -2 ........ **OK**

.................................................. ................................................

(iii) 6x(2) + 7x - 4 = 0

Using Quadratic Equation ( to 3 d.p)

__- 7__ +- __sqrt 7(2) - (4 x 6 (-4)__

2x6 2x6

-0.583 +-__ 12.041__

12

x = 0.420 x = - 1.587 ........ **OK**

.................................................. .................................................

(iv) -7 + 11x - 3x(2) = 0

Using Quadratic Equation ( to 3 d.p)

***** do i transpose this so that x(2) is at the front***** ........ **Yes**

**3x(2) - 11x + 7 = 0 ???? (x = 0.550 x =-4.220)** ........ **Where did you get these results from?**

...